Food and Drug Administration perspective: Advancing product development for non-healing chronic wounds. - Dev Verma, Kapil; Lewis, Felisa; Mejia, Maryjoy; Chalasani, Meghana; Marcus, Kendall A. (Wound Repair & Regeneration)
The US Food and Drug Administration (FDA) understands that innovative product development is essential to addressing the unmet medical need of non-healing chronic wounds. Barriers to product development for non-healing chronic wounds may involve but are not limited to a dearth of biological models, challenges in drug delivery, challenges in clinical trial execution, and limited commercial viability. This perspective article discusses FDA's renewed focus on non-healing chronic wounds and outlines efforts to address identified barriers to product development for nonhealing chronic wounds. In collaboration with key wound healing stakeholders including academia, professional associations, patient groups, reimbursement organizations and industry, FDA intends to help advance product development for non-healing chronic wounds for the ultimate betterment of patients.